ATP-Binding Cassette transporters' gene expression in pediatric patients with acute leukemia; a comprehensive analysis of published reports through PubMed search engine - Mehrvar, Narjes; Akbari, Mohammad Esmail; Rezvany, Mohammad Reza; Abolghasemi, Hasan; Saberynejad, Javad; Mehrvar, Azim; Faranoush, Mohammad; Keramatinia, Ali Asghar; Shekarriz-Foumani, Reza; Movafagh, Abolfazl (Cellular and Molecular Biology, 2019)
Multidrug resistance based on ABC transporters' gene expression is one of the most important health challenges through chemotherapy of patients. This resistance can cause relapse or treatment failure. The goal of this conducted study was to evaluate the results of published reports which considered ABC transporters' gene expression in pediatric patients with acute leukemia. PubMed as a free search engine was chosen. The following Mesh terms were used as: "ATP-binding cassette transporters” OR "ABC-transporters*” AND "gene expression*” AND "leukemia” OR "ALL” OR "AML” OR "acute leukemia*”. Age was set as an additional filter with the age range of birth to 18 years old. Initial screening was performed according to inclusion and exclusion criteria and the quality of the selected papers was assessed. Papers categorized into three sections as: pediatric patients with ALL (6 papers from 1998-2015); pediatric patients with AML (3 papers from 1992-2011) and pediatric patients with ALL and AML (7 papers from 1992-2014). Totally 1118 patients enrolled in the searched studies (ALL and AML: 488; ALL: 405; AML: 225). The common method for evaluating gene expression of ABC transporters was RT-PCR. More than 50% of the papers showed the influence of ABC transporters' gene expression on prognosis and treatment failures of patients. Despite controversial results, the gathered information in the current report serves as a comprehensive referential resource, which can be beneficial for future planning around this title, especially in developing countries.